2016
DOI: 10.1089/bfm.2015.0134
|View full text |Cite|
|
Sign up to set email alerts
|

Beyond Necrotizing Enterocolitis Prevention: Improving Outcomes with an Exclusive Human Milk–Based Diet

Abstract: Objective: The aim of this study was to compare outcomes of infants pre and post initiation of a feeding protocol providing an exclusive human milk–based diet (HUM).Materials and Methods: In a multicenter retrospective cohort study, infants with a birth weight <1,250 g who received a bovine-based diet (BOV) of mother's own milk fortified with bovine fortifier and/or preterm formula were compared to infants who received a newly introduced HUM feeding protocol. Infants were excluded if they had major congenital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
154
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(165 citation statements)
references
References 17 publications
7
154
0
4
Order By: Relevance
“…There were 17 cohort studies21–26 30–38 40 41 and 5 RCTs 20 27–29 39. The sample sizes varied from 5230 to 158721. Most of the BPD diagnostic criteria were oxygen dependency at 28 days or more after birth or 36 weeks postmenstrual age (PMA),20–25 27–29 31 33 35 36 38–41 pulmonary radiography20 and chest X-ray24 abnormalities, and prolonged mechanical ventilation30; however, the definition of BPD in the four studies was unknown 26 32 34 37…”
Section: Resultsmentioning
confidence: 99%
“…There were 17 cohort studies21–26 30–38 40 41 and 5 RCTs 20 27–29 39. The sample sizes varied from 5230 to 158721. Most of the BPD diagnostic criteria were oxygen dependency at 28 days or more after birth or 36 weeks postmenstrual age (PMA),20–25 27–29 31 33 35 36 38–41 pulmonary radiography20 and chest X-ray24 abnormalities, and prolonged mechanical ventilation30; however, the definition of BPD in the four studies was unknown 26 32 34 37…”
Section: Resultsmentioning
confidence: 99%
“…Despite various strategies aimed at decreasing BPD, the incidence remains high for premature infants. In a recent retrospective multicentre study, an exclusive human milk-based diet was shown to decrease the incidence of BPD, NEC, retinopathy of prematurity and death 3. Patel and colleagues’ study is the first to evaluate the impact of OMM on the risk of BPD and associated costs.…”
Section: Contextmentioning
confidence: 99%
“…[14][15][16] However, investigations of the impact of human milk (OMM±donor milk supplementation) on BPD are limited. [17][18][19] The purpose of this study was to investigate the dose-dependent impact of OMM feedings received from birth to 36 weeks PMA on BPD and associated NICU healthcare costs in a contemporary cohort of VLBW infants.…”
Section: Introductionmentioning
confidence: 99%